An integer linear programming model of a university course timetabling problem (2008)
In this study, the combinatorial problem of university course timetabling of an Engineering Faculty of a Nigerian university (the University of Ibadan) was addressed. The problem of assigning lecturers, rooms, and courses to fixed timeslots, normally, a week, while satisfying a number of problem-specific constraints was modeled as an Integer Linear Programming (ILP). The problem constraints have been divided into hard constraints and soft constraints. While the hard constraints constitute the problem constraints, the minimization of the violation of the soft constraints constitutes the objective function. Being an NP-Hard problem, a heuristic was developed and implemented manually. Ten (10) solutions were generated manually from 10 runs with the newly developed search technique. An analysis of the performance of the solutions shows that the proposed heuristic is promising.